2019
DOI: 10.3390/molecules24061101
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Analysis and Anti-Oxidative Property of Naoxinqing Tablet, a Proprietary Preparation of Diospyros Kaki Leaves

Abstract: The Naoxinqing (NXQ) tablet is a standardised proprietary herbal product containing an extract of persimmon leaves (Diospyros kaki) for the management of cardio- and cerebrovascular diseases. Although previous reports suggested that the efficacy of NXQ is at least partly mediated by its anti-oxidative property, the anti-oxidative effect of the major components of NXQ has not been studied systematically. For quality control purposes, only analytical methods limited to 3 marker analytes have been reported, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Finally, a compound was putatively annotated when it has been previously reported from either the studied plant or one of the species of the genus [ 18 , 20 , 27 , 28 , 29 ] and its MS characteristics matched with fragmentation patterns listed above. The other compounds were annotated by comparison of their respective MS characteristics with reported MS data in the literature [ 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a compound was putatively annotated when it has been previously reported from either the studied plant or one of the species of the genus [ 18 , 20 , 27 , 28 , 29 ] and its MS characteristics matched with fragmentation patterns listed above. The other compounds were annotated by comparison of their respective MS characteristics with reported MS data in the literature [ 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…NXQ prepared from PL is used for the management of cardio- and cerebrovascular diseases, and its composition was investigated using UPLC coupled with a tandem MS [ 42 ]. Seven compounds, specifically kaempferol-3- O -glucoside (astragalin), quercetin-3- O -glucoside (isoquercitin), quercetin-3- O -galactoside (hypericin), kaempferol, quercetin, pyromucic acid, and protocatechuic acid were identified in the NXQ.…”
Section: Bioactive Compounds Of Plmentioning
confidence: 99%
“…Results suggested that harvest time and variety were important factors for antioxidant activity, mainly those harvested in months with higher ambient temperature, sunshine duration, and solar radiation. Moreover, Kazzem et al [ 42 ] determined the antioxidant activity of NXQ tablets prepared from PL. It was found that flavonoids, mainly quercetin and kaempferol, showed strong DPPH radical scavenging activity and inhibited the H 2 O 2 -induced human vascular endothelial (EA.hy926) cell injury and intracellular ROS generation.…”
Section: Pharmacological Effects Of Plmentioning
confidence: 99%
“…Among them, phenolic acids such as gallic acid, caffeic acid, chlorogenic acid, and cinnamic acid, and flavonoids such as kaempferol-3-Oglucoside, isoquercitrin, quercetin, hyperoside, and rutin, are present in persimmon leaves [8]. At present, there is no effective assay to evaluate the content of these phenolics comprehensively, and the existing studies only determine a small amount of those compounds [9,10]. Therefore, the contribution of different compounds to antioxidant activity is still unclear.…”
Section: Introductionmentioning
confidence: 99%